Correlative atomic scale characterisation of secondary carbides in M50 bearing steel. Issue 9 (24th March 2018) - Hopkin, Sarah E.; Danaie, Mohsen; Guetard, Gael; Rivera-Diaz-del-Castillo, Pedro; Bagot, Paul A. J.; Moody, Michael P.
Abstract: Correlative atom probe tomography (APT) and transmission electron microscopy (TEM) are used to characterise the microstructure and chemistry of carbide precipitation in M50 bearing steel. This is a prerequisite in establishing relationships between the microstructure and hydrogen embrittlement (HE) resistance. Secondary carbides are the focus of this study, as they play a major role in improving HE-resistance. Secondary carbides are observed in APT, with compositions close to M4 C3, M2 C and M3 C. Correlative TEM measured orientation relationships between the martensite matrix and carbides, enabling the confirmation of M3 C cementite precipitates in the corresponding APT reconstruction. Additionally, other precipitates observed in TEM were correlated to the M2 C carbides in APT data. The M4 C3 carbides are found to have a significantly lower volume fraction than the M2 C carbides.